Population dynamics of the mud crab Panopeus austrobesus Williams, 1983 (Brachyura: Panopeidae) associated with a mussel farm at the southeastern Brazilian coast - Camargo, Flavio de Vasconcelos (2019)
Made available in DSpace on 2019-09-11T20:58:34Z (GMT). No. of bitstreams: 0 Previous issue date: 2017